2017
DOI: 10.26420/austinjdent.2017.1071
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implants in Osteoporotic Patients Taking Oral Bisphophonates: A Literature Review

Abstract: Objective: Osteoporosis is a systemic disorder characterized by generalized decrease in bone mineral density that can eventually result in fragility fracture. Bisphosphonates have been used in the treatment of osteoporosis for many years in order to inhibit bone resorption. Unfortunately, the use of bisphosphonates has been found to be associated with several adverse events in patients where dental pathologies were present. For this reason, an increased attention has been recommended in those patients where bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Patients with osteoporosis display a range of skeletal changes that may impact on the possibility of placing dental implants without the need for bone augmentation. Nuti et al reported findings are a greater alveolar ridge resorption than average altered trabecular pattern in the anterior maxilla and posterior mandible erosions of the inferior border of the mandible as compared to unaffected individuals and increased resorption and thinning of the mandibular inferior cortical margin [5]. There are anecdotal reports that in patients with osteoporosis the incidence of maxillofacial fractures during the placement of endosseous implants is increased [6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with osteoporosis display a range of skeletal changes that may impact on the possibility of placing dental implants without the need for bone augmentation. Nuti et al reported findings are a greater alveolar ridge resorption than average altered trabecular pattern in the anterior maxilla and posterior mandible erosions of the inferior border of the mandible as compared to unaffected individuals and increased resorption and thinning of the mandibular inferior cortical margin [5]. There are anecdotal reports that in patients with osteoporosis the incidence of maxillofacial fractures during the placement of endosseous implants is increased [6].…”
Section: Discussionmentioning
confidence: 99%